Blame-Liability, Inviting Trust, & Beginning a New Account of Promising - (:unkn) unknown (My University, 2021)
In this paper, I argue the two examples present a problem for two accounts of promising, and in light of these problems, I create the beginning of an alternative account of promising. The first example shows a problem with Jack Woods’ account of promising, while the second shows a problem for a trust view developed by Daniel Friedrich and Nicholas Southwood. In light of these criticisms, I start to develop my own view where promising gives the promisor a claim-based reason for keeping their promise, and though not strictly promising, an invitation to trust plays an important explanatory role, particularly by providing an error theory and explaining the distinctive sense in which one can feel betrayed when some promises are broken.